Behavioural intentions to adopt mobile wallets: a developing country's perspective. Issue 3 (15th August 2016) - Madan, Khushbu; Yadav, Rajan
Abstract : Purpose: This paper aims to understand the factors that affect consumers' adoption of mobile wallets as an alternative method of making payments to purchase goods and services. Design/methodology/approach: A survey of over 210 mobile phone consumers was made. The study added two additional constructs - perceived regulatory support (PRS) and promotional benefits (PBs)- and proposed an integrated approach to understanding mobile wallet adoption. The hypothesized relationships were analysed via structural equation modelling. Findings: The results indicated performance expectancy (PE), social influence (SI), facilitating conditions (FC), perceived risk (PR), perceived value (PV), PRS, as well as PBs, to be significant factors in predicting behavioural intentions (BI) to adopt mobile wallet solutions. The impact of effort expectancy (EE) was found to be statistically insignificant. Research limitations/implications: The small sample size, and the possibility of including new variables such as personal innovativeness, which have not been addressed here, are some of the limitations of this study. Practical implications: The findings of this paper would be useful for mobile wallet service providers, mobile app writers and institutions involved in the facilitation and regulation of such services to develop suitable strategic frameworks to encourage the adoption of mobile wallets. Originality/value: The study is the first of its kind in India and has added a new dimension in the assessment of technology adoption by proposing two new variables.